Understanding the compactness of employment activities in high-density cities through cellphone location data. (July 2021) - Zhou, Xingang; Lang, Wei; Yeh, Anthony GO; Niu, Xinyi
Urban development in many cities worldwide presents a dispersed development with urban sprawl and excessive land use. Compact city development facilitates an efficient use of land that aims to reduce excessive land consumption and commuting. However, the ignorance of the relationships between land use and the compactness of employment activities has resulted in excessive commuting. The separation of jobs and housing due to functional zoning has caused criticism in compact city development. This research aims to examine the compactness of workers' employment activities and its relationship with land use to enrich our knowledge on compact city development. The relationship between urban and employment activity compactness is examined through cellphone location data in Shanghai, China. A set of indicators, including intrazonal employment ratio and interzonal commuting distance, are examined to measure the compactness of employment activities. Land-use compactness is measured through building density, land-use diversity, and accessibility. The effect of land-use compactness on employment activity compactness is analyzed through structural equation modeling. A high proportion of residential land use reduces the intrazonal employment ratio and increases the average interzonal commuting distance. A high proportion of industrial and commercial land use increases the intrazonal employment ratio. These are the spatial characteristics to improve urban compactness. This study contributes to decision-making for compact development, which is of great significance to promoting compact activities. It can also provide spatial planning policies that facilitate workers' access to local employment opportunities with short travel distances through land use planning for mixed land use.